If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9x + -4)(3x + 7) = 0 Reorder the terms: (-4 + 9x)(3x + 7) = 0 Reorder the terms: (-4 + 9x)(7 + 3x) = 0 Multiply (-4 + 9x) * (7 + 3x) (-4(7 + 3x) + 9x * (7 + 3x)) = 0 ((7 * -4 + 3x * -4) + 9x * (7 + 3x)) = 0 ((-28 + -12x) + 9x * (7 + 3x)) = 0 (-28 + -12x + (7 * 9x + 3x * 9x)) = 0 (-28 + -12x + (63x + 27x2)) = 0 Combine like terms: -12x + 63x = 51x (-28 + 51x + 27x2) = 0 Solving -28 + 51x + 27x2 = 0 Solving for variable 'x'. Factor a trinomial. (-7 + -3x)(4 + -9x) = 0Subproblem 1
Set the factor '(-7 + -3x)' equal to zero and attempt to solve: Simplifying -7 + -3x = 0 Solving -7 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -3x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -3x = 0 + 7 -3x = 0 + 7 Combine like terms: 0 + 7 = 7 -3x = 7 Divide each side by '-3'. x = -2.333333333 Simplifying x = -2.333333333Subproblem 2
Set the factor '(4 + -9x)' equal to zero and attempt to solve: Simplifying 4 + -9x = 0 Solving 4 + -9x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -9x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -9x = 0 + -4 -9x = 0 + -4 Combine like terms: 0 + -4 = -4 -9x = -4 Divide each side by '-9'. x = 0.4444444444 Simplifying x = 0.4444444444Solution
x = {-2.333333333, 0.4444444444}
| (3/5)=(w-5)/2 | | -(-8x)=(-38) | | (3/5)=(w-5)/2) | | 2cosx*sinx=-cosx | | 24-20= | | 44+d+2(30-4d)=d | | 2cos(x)sin(x)=-cos(x) | | 3(x-5)=2(x+3) | | 24-10= | | -7x+17=-18 | | 10.5-8.4= | | 7(x-3)=5(x+5) | | 114+32= | | 9+10n=21 | | .512x+.125(x-2)=.725 | | 2x+5=12x-6 | | 7(x)-5=2(x+10) | | N+5k=245 | | (a^3/-2b^2)^4 | | 2a(4-6)=40 | | 4y+1=5y+2 | | 32+8n=47 | | (3-4y)7= | | 625x^8=9 | | (20x^-4/27y^2)/(8x^-3/15y^-5) | | (-3/2)=(-2/3v)-(8/5) | | (u^2/-5v^4)^3 | | 81-u^2=0 | | 2.25x=2.5x | | 35000+1680b=175000 | | 3(v-1)=7v+1-2(-2v-7) | | 4(5+3m)=128 |